Chapter Tra ricerca storica, Citizen e Public History: il Centenario della scuola elementare Fortuzzi di Bologna - Carpigiani, Carla (Studi e saggi, 2019)
In 2017, the teachers of the Fortuzzi primary school in Bologna, as part of the school's centenary initiatives, conducted a public and participatory research on its history that involved pupils, parents and the neighbourhood. The essay summarizes this research path and reflects on the characteristics of this particular type of collective historical research.